Innovation and organizational performance: A perspective among Chinese enterprises - Zhu, Chengpeng; Isaac, Adubofour; Edmund, Nkrumah Nana Kwame (Frontiers in Psychology, 2022)
The influence of innovation on the performance of Chinese enterprises still remain inconclusive in the literature of innovation management. The aim of this research therefore is to examine the link between innovation and performance of Chinese enterprises, and explore the influence of sentiment expressed by investors in this relationship. The data for our study is drawn from 3500 Chinese listed firms, operating within the periods, 2009 to 2017. Panel autoregressive models (fixed and random effects) are employed in our empirical analyses. We further performed Hausman tests in order to ascertain which of the models is more suitable for our dataset. Results from the analysis show that innovation significantly influence the performance of Chinese enterprises and it is moderated by sentiment expressed by investors. Specifically, it is found that Chinese enterprises tend to be innovative as feedback to sentiment expressed by investors and this consequently results in higher performance.